Paradigma Baru Pendidikan Islam - Shopian Hidayatulloh, Haeru Taofiqillah, Sazli Rais, (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
This study examines the new paradigm of Islamic education, with the aim of the research is to understand, identify and know the actualization of the new paradigm of Islamic education. Meanwhile, the research contribution presented is to realize and actualize the new paradigm of Islamic education. Furthermore, this research is library research using descriptive and analytical methods. These two methods are not presented separately, but are actualized in an integrated manner. The descriptive method is used, because in its presentation it will provide a general illustration of the problem to be studied, then a comprehensive interpretation will be made from the data. While the analytical method is used to look critically at the various problems that underlie the problems in question. While the data processing procedure, used Content Analysis. This is of course the researcher conducts an analysis of the validity of the instrument or data to be measured, through a process of data processing stages so that the data is ready to be interpreted, concluded and verified with grand theory as the analysis. Based on the above context, the research findings indicate that the actualization of the new paradigm of Islamic education through the realization of three substantive dimensions of Islamic education, namely the cognitive, affective and psychomotor dimensions. The first meaning is the acquisition of students to science; while the second meaning is the realization of students towards science in the form of their attitudes or behavior towards learning environment even to society; while the third meaning synergism between the knowledge gained with their attitudes or behavior which is actualized in everyday life.